Academic Writing in the 21st Century: Voices from English and Indonesian Lecturers - Saepa Wastam; Lala Bumela; Septi Gumiandari (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2023)
Academic writing is a general skill that must be mastered by every college graduate, especially those majoring in English Language Education. However, according to the latest research, academic writing is the most neglected language skill in education in Indonesia. It is believed that poor and outdated pedagogy as well as the low quality of teachers are the main factors that makes academic writing more challenging to learn. Furthermore, in the context of 21st century, each learner should be equipped with bi/multilingual proficiency as a key instrument for global communication, and, therefore, a sound language pedagogy is the one that helps learners to develop their bilingual academic proficiency. This current study critically gathered insights from six respondents on the nature of academic writing both in English and in Bahasa Indonesia and the role it plays in the acceleration of knowledge building in their own fields. Qualitative research was employed. The collected voices were transcribed and analyzed in the forms of thematic analysis and word clouds. The results of the study show that the respondents (especially the lecturers) have not provided key arguments on how bilingual academic literacy should be approached. However, other respondents believed that academic writing (pedagogy and assessment) should be approached differently. In other words. Innovation in academic literacy pedagogy in Indonesia should be addressed soon. This study concludes that it takes more time and effort to conceptualise the notion of bilingual academic literacy in Indonesian higher education context. This study is expected to provide key insights on how innovation on academic literacy innovation should be addressed.